Two different characteristics and prognosis of grade 3 gastroenteropancreatic neuroendocrine tumors (Annals of Medical Research, 2023)
Aim: Grade 3 gastroenteropancreatic neuroendocrine tumors (GEPNETs) are not a homogenous group, and this work aims at determining clinicopathologic, survival and prognostic differences in metastatic grade 3 GEPNETs with the help of Ki-67(mitotic index) and GA-68 PET CT/octreoscan.Materials and Methods: Patients diagnosed with metastatic grade 3 GEPNETs were divided into two groups based on the Ki-67 cut-off point, 47, as Ki-67 low and high. Again, the patients were divided into two groups according to scan positivity, and all four groups were compared on the basis of clinicopathologic characteristics, survival and prognostic factors.Results: Twenty-six patients were included in the study. The median overall survival in low group was 20 months and 10 months in high group (p=0.321). Lower Ki-67 scan positive group had longer overall survival than lower Ki-67 scan negative group (NR vs 3 months, respectively, p=0.067). In the high Ki-67 group, the median overall survival was longer in scan positive than negative group (10 vs 9, respectively, p=0.956).Conclusion: The median overall survival was longer in patients with low Ki-67 levels compared to high Ki-67 levels. The best overall survival was in low Ki-67 and scan positive group.
Keywords: Gastroenteropancreatic; Neuroendocrine; Grade